Innovating SI Units in Maxwell's Equations. Evolutionary Approach to Electrodynamics as an Alternative to the Time-Harmonic Field Concept - Tretyakov, Oleg A. (IEEE, 2018)
A novel Ihrmat of Maxwell's equations in SI units is proposed. To this aim, the original field vectors, E and N, are scaled by the specially introduced factors, carrying dimension of volt and ampere, respectively. Maxwell's equations in novel Ihrm at involve only one dimensional physical constant, namely: the speed of light in vacuum. Maxwell's equations in that format are applied for studying propagation in waveguides of the time varying waveforms (signals). To this aim, a simplified waveguide version of the evolutionary approach to electrodynamics is presented. Ultimately, modal amplitudes of the signals are expressed via solutions to Klein-Gordon equation, the arguments of which involve axial coordinate z and thne 1 as variables.
2nd URSI Atlantic Radio Science Meeting (AT-RASC) -- MAY 28-JUN 01, 2018 -- Meloneras, SPAIN
Keywords: Klein-Gordon Equation; Wave-Guide; Modal Waves; Cavity